Pelvic floor reconstructive surgery under local anesthesia: A systematic review and meta‐analysis. Issue 6 (19th June 2021) - Zacharakis, Dimitrios; Prodromidou, Anastasia; Douligeris, Athanasios; Hadzilia, Sofia; Kathopoulis, Nikolaos; Athanasiou, Stavros; Grigoriadis, Themos
Abstract: Aims: The decision on the appropriate type of anesthesia for pelvic floor repair depends on a variety of factors including patients' age, performance status, comorbidities, cost‐effectiveness and personal preferences. We aim to review the literature on urogynecological procedures performed under local anesthesia (LA). Methods: A systematic search of four electronic databases was conducted for articles published up to May 2020. Studies reporting outcomes of women who underwent pelvic floor reconstructive surgery under LA with or without sedation, were considered eligible. Results: Nineteen studies (14 noncomparative and 5 comparative), including 1626 cases of urogynecological procedures under LA were recruited. Meta‐analysis revealed significantly lower mean pain scores in LA group compared to general‐regional anesthesia one (GA/RA) at both 4–6 h and 8–18 h postoperatively (160 patients; mean difference [MD], −1.70; 95% confidence interval [CI]: −3.12, −0.28; p = 0.02 and 160 patients; MD, −0.72; 95% CI: −1.17, 0.27; p = 0.002, respectively). Pain scores at >24 h did not differ among the two groups (160 patients; MD, −0.28; 95% CI: −0.60–0.05; p = 0.10). Intra‐ and postoperatively morphine use was not different among patients who received LA and GA during prolapse surgery while nausea rates were significantly lower in LA group compared to RA group 8 h postoperatively. Conclusions: LA with or without sedation represents a safe and efficient alternative anesthetic technique for urogynecological procedures with improved pain scores in up to 18 h postoperatively especially in patients who underwent surgery for SUI. LA is feasible and could be offered to patients undergoing pelvic floor surgery allowing a prompt postoperative recovery.